2001
DOI: 10.1080/02724930120077835
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of multi-drug-resistantAcinetobacter anitratusspecies in neonatal and paediatric intensive care units in a developing country: concern about antimicrobial policies

Abstract: Antimicrobial abuse is a serious risk factor for the emergence of multi-drug-resistant (MDR) pathogens. We report on the emergence of multi-drug-resistant Acinetobacter anitratus species over two 8-week periods in 1999 in the neonatal and paediatric intensive care units (NICU and PICU) of King Edward VII Hospital, Durban, South Africa. The source, transmission dynamics, microbiological evaluations, antibiotic utilization patterns and outcome were evaluated. MDR Acinetobacter anitratus was isolated from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
1
28
1
1
Order By: Relevance
“…infections in pediatric patients have shown even higher levels of nonsusceptibility to ciprofloxacin (99 -100%), 11,25 and to thirdgeneration cephalosporins (92-100%), 11,21,25 ticarcillin/clavulanate (96%), 11 and imipenem (62-100%). 8,11 Previous pediatric studies have not examined resistance to TMP-SMX. Unlike our study, Gales et al 9 found that the frequency of resistance to antibiotics in hospital-acquired Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…infections in pediatric patients have shown even higher levels of nonsusceptibility to ciprofloxacin (99 -100%), 11,25 and to thirdgeneration cephalosporins (92-100%), 11,21,25 ticarcillin/clavulanate (96%), 11 and imipenem (62-100%). 8,11 Previous pediatric studies have not examined resistance to TMP-SMX. Unlike our study, Gales et al 9 found that the frequency of resistance to antibiotics in hospital-acquired Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Little attention has been given to the aetiology, prevention and management of paediatric VAP in South Africa, with only one paper published in the last 10 years relating to nosocomial infection in South African PICUs 9 . This is the first study to specifically investigate VAP in the context of a South African PICU with high HIV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…[54] Jeena et al described a multi-drug resistant Acinetobacter anitratus outbreak in a pediatric and neonatal ICU causing 23 infections, primarily post-operative infections and pneumonia, with a 57% mortality rate. [55] Birth weight < 1000 grams and receipt of prolonged antibiotic therapy (>21 days) have been associated with increased risk of infections caused by antibiotic resistant GNB. In developing countries, where GNB cause a larger proportion of neonatal sepsis than in developed countries, the burdens of resistance are even greater.…”
Section: Clinical Impact Of Antimicrobial Resistant Pathogensmentioning
confidence: 99%